COMPARATIVE ANALYSIS OF THE GREEDY METHOD AND DYNAMIC PROGRAMMING IN SOLVING THE KNAPSACK PROBLEM (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
In this work, two of the existing algorithms for solving the Knapsack are investigated and implemented using the same programming language. The complexity of the programs and hence the algorithms were measured to determine the more efficient of the two algorithm. The result of this comparative study of complexity is that Greedy algorithm is more efficient for solving knapsack problem than dynamic programming approach